ENVIRONMENTAL MANAGEMENT IN THE TEACHING OF ANALYTICAL CHEMISTRY - Espinosa Descalzo, Espinosa Descalzo (2020)
This article was written with the objective of stimulating reflection on the commitment of teachers to be updated on environmental issues and introduce the Environmental Education subject in the development of the main theoretical and practical contents of the Professional School Chemistry courses on the training of future professionals. These individuals besides of mastering science in their field and range of action, should deepen in the commitment to the environment with sufficient rigor, besides minimizing the harmful emissions their activities would generate in order to contribute to sustainable development. One way to include the principles of Environmental Education is through participatory management in laboratory practices based on the principle of source reduction which, in addition to helping environmental preservation, can generate economic benefits such as reduction in reagent consumption of order 33.33 to 80 %. Furthermore, it fosters the exercise of the critical thinking of the student and motivates their active participation as a citizen in terms of environmental problems, which are not only exclusive to the field of technology, but it also has the social responsibility of forming values, good habits and behaviors that influence people around them.